Young and lonely : the social conditions of loneliness - Batsleer, Janet; Duggan, James (Research fellow) (Policy Press, 2021)
"Anchored in accounts of young people's personal experiences of loneliness, this book addresses important questions about tackling today's epidemic of loneliness among young people. It explores experiences of loneliness in early life, how it is navigated when first encountered and considers how social conditions of poverty, precarity, inequality and competitive pressures to succeed can dramatically influence these feelings. Presenting diverse and nuanced social accounts of loneliness, the authors explore ways to harness the creative and positive potential of loneliness and provide evidence-based recommendations for policy makers, practitioners and young people to help tackle the crisis."